PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GAME EDUKASI TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA UPT SD NEGERI 107 INPRES KUNJUNG KABUPATEN TAKALAR - Reski Aulia; Andi Syukri Syamsuri; Ummu Khaltsum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The main problem of this research is that the learning process is still dominated by the use of conventional methods that are centered on the teacher (teacher-centered). Teachers more often use lecture methods and giving assignments, so that interaction in learning is less than optimal. This condition causes student engagement in learning to remain low. Only a small number of students are active in answering questions or providing responses, while most students tend to be passive and less participating during the learning process. This study aims to determine the Effect of Using Educational Game Learning Media on Improving Fourth Grade Student Learning Outcomes in Indonesian Language Subjects at UPT SD Negeri 107 Inpres Kunjung, Takalar Regency. The type of research used in this study is Quantitative, namely a type of research that only involves one experimental class without a comparison group. The design of this study is One Group Pretest-Posttest Design. The pretest is given before treatment and the posttest is given after treatment. The sample in this study is fourth grade students consisting of 12 male students and 12 female students. Data collection techniques are carried out using tests and observations. The data analysis technique in this study used descriptive and inferential statistics (t-test). The descriptive statistics showed that the average score for listening skills before using the Educational Game media was 55.41, while the average score for listening skills after using the Educational Game media was 92.91. This indicates a difference in students' listening skills before and after using the Educational Game media in learning. The t-test analysis results showed that the calculated t value was 2.069, and the t table = 8.378. Therefore, the calculated t = 2.069> t table = 8.378, which means H0 is rejected and H1 is accepted. Therefore, it can be concluded that the Educational Game media is effective in improving the listening skills of fourth-grade students at the UPT SD Negeri 107 Inpres Kunjung, Takalar Regency.